Facilitators and barriers to the implementation of a Mobile Health Wallet for pregnancy-related health care: a qualitative study of stakeholders’ perceptions in Madagascar - Muller, Nadine; McMahon-Rössle, Shannon A.; De Neve, Jan-Walter; Funke, Alexej; Bärnighausen, Till; Rajemison, Elsa; Lacroze, Etienne; Emmrich, Julius; Knauss, Samuel (PLOS ONE, 2020)
Financial barriers are a major obstacle to accessing maternal health care services in low-resource settings. In Madagascar, less than half of live births are attended by skilled health staff. Although mobile money-based savings and payment systems are often used to pay for a variety of services, including health care, data on the implications of a dedicated mobile money wallet restricted to health-related spending during pregnancy-a mobile health wallet (MHW)-are not well understood. In cooperation with the Madagascan Ministry of Health, this study aims to elicit the perceptions, experiences, and recommendations of key stakeholders in relation to a MHW amid a pilot study in 31 state-funded health care facilities. We conducted a two-stage qualitative study using semi-structured in-depth interviews with stakeholders (N = 21) representing the following groups: community representatives, health care providers, health officials and representatives from phone provider companies. Interviews were conducted in Atsimondrano and Renivohitra districts, between November and December of 2017. Data was coded thematically using inductive and deductive approaches, and found to align with a social ecological model. Key facilitators for successful implementation of the MHW, include (i) close collaboration with existing communal structures and (ii) creation of an incentive scheme to reward pregnant women to save. Key barriers to the application of the MHW in the study zone include (i) disruption of informal benefits for health care providers related to the current cash-based payment system, (ii) low mobile phone ownership, (iii) illiteracy among the target population, and (iv) failure of the MHW to overcome essential access barriers towards institutional health care services such as fear of unpredictable expenses. The MHW was perceived as a potential solution to reduce disparities in access to maternal health care. To ensure success of the MHW, direct demand-side and provider-side financial incentives merit consideration.
Gesehen am 25.09.2020